Efek sitotoksik ekstrak buah kapulaga jawa (Amomum compactum Soland. Ex. Maton) - Nailul Muna; Noni Zakiah; Vonna Aulianshah; Munira Munira; Amelia Sari (Jurnal SAGO Gizi dan Kesehatan, 2019)
Background: In developed countries cancer is the second leading cause of death after cardiovascular disease. Cancer prevention can be done with synthetic or traditional medicine. However, synthetic treatments often cause side effects and of course require high costs. Java Cardamom (Amomum compactum Soland. Ex Maton) is a plant that contains antioxidants. Antioxidants can inhibit oxidation reactions by binding to free radicals and molecules that are very reactive so that cell damage can be prevented. Cardamom contains flavonoids which can induce cell death programs as well as tannins as free radical scavengers.Objectives: This study aims to determine the LC50 value of Java cardamom (Amomum compactum Soland. Ex Maton) on Artemia salina Leach.Methods: This study was an experimental study using a completely randomized design (CRD) using 180 artemia larvae which were divided into 6 treatment groups. Each group included 10 artemia larvae with varying concentrations of 500 ppm, 250 ppm, 100 ppm, 50 ppm, 10 ppm and 0 ppm (not given extract). Three repetitions were performed for each concentration.Results: The results showed from the observations obtained the LC50 value of Java cardamom extract is 26.60 ppm. So that the Java cardamom extract (Amomum compactum Soland. Ex Maton) has the potential as an anticancer (cytotoxic).Conclusion: Java cardamom extract (Amomum compactum Soland. Ex Maton) is active and can be developed as an anticancer compound.